Subsidiary Role of Women in Warfare in Ilorin Emirate in the Nineteenth Century - Oladimeji Mohammed Alabi (LAPAI JOURNAL OF NIGERIA HISTORY, 2021)
In many precolonial African societies, war was regarded as an exclusively masculine sojourn. Consequently, studies on precolonial warfare have concentrated on the role of men leading to a paucity of literature on the contribution of women in military activities. The objective of this study is to examine the role of women in precolonial wars in Ilorin, particularly, in the wars of establishment, expansion and consolidation of her emirate in the Nineteenth Century. The historical research method comprising oral interviews as primary sources, and written materials as secondary sources, was employed in the study. The contributions of women to Ilorin economy has enjoyed considerable attention from scholars, particularly in vocations like agriculture, commerce and indigenous industries in the production of beads, pots and traditional cloth. However Ilorin women’s subsidiary role in military has not been so captured. This is partly due to Yoruba belief, as in much of African societies, that military service was the exclusive domain of the men; and also because of the influence of Islam on Ilorin, which excluded women from military service. This study however, discovered that the Ilorin women played significant subsidiary roles in facilitating success for the men. These include cooking, reparation of herbs for treating wounded warriors, advising warriors and giving spiritual support in the form of prayers. Women were also used as spies on the enemy and were good tools for thwarting the plans of the opponents. One remarkable role of Ilorin women in the military was the delivery of praise songs and chants in appellation of the warriors, particularly the Baloguns. It was common to find women who were versed in the cognomen and agnomen of warriors in Ilorin, particularly in the compounds of the warriors. Their role was to boost the morale of the soldiers and to caution them on critical issues concerning the prospective mission. The study concluded that even though Ilorin women did not bear arms like the men, their contribution to the emirate’s wars of defence and consolidation were quite significant.